2017
DOI: 10.1186/s12936-017-2038-y
|View full text |Cite
|
Sign up to set email alerts
|

Household costs among patients hospitalized with malaria: evidence from a national survey in Malawi, 2012

Abstract: BackgroundWith 71% of Malawians living on < $1.90 a day, high household costs associated with severe malaria are likely a major economic burden for low income families and may constitute an important barrier to care seeking. Nevertheless, few efforts have been made to examine these costs. This paper describes household costs associated with seeking and receiving inpatient care for malaria in health facilities in Malawi.MethodsA cross-sectional survey was conducted in a representative nationwide sample of 36 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 25 publications
8
37
0
Order By: Relevance
“…The average indirect cost (GH¢25.04/US$6.59) was 1.7 times higher than the direct cost (GH¢14.87/US$3.91). This is consistent with many findings where the indirect costs of malaria treatment were higher than the direct costs of treatment [11,15,33,37,38]. Therefore, efforts to improve access to health care and reduction of financial burden to households in the treatment of malaria should not only be directed to direct medical costs but also indirect costs.…”
Section: Discussionsupporting
confidence: 89%
“…The average indirect cost (GH¢25.04/US$6.59) was 1.7 times higher than the direct cost (GH¢14.87/US$3.91). This is consistent with many findings where the indirect costs of malaria treatment were higher than the direct costs of treatment [11,15,33,37,38]. Therefore, efforts to improve access to health care and reduction of financial burden to households in the treatment of malaria should not only be directed to direct medical costs but also indirect costs.…”
Section: Discussionsupporting
confidence: 89%
“…This was comparable to a study done in other settings elsewhere. 6,7,9,10,14,23 The higher indirect costs of malaria illness may be due to the fact that the costs of anti-malarial drugs and diagnostics or testing were subsidized or free at public health sector of Ethiopia. 17 Nonetheless, a significant proportion of households' total costs of malaria illness (22.3%) was also attributed to direct costs.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly the poorer and vulnerable households are at increased risk of the burdens of malaria and the cost of malaria is far worse for complicated cases. [6][7][8][9][10] The environmental and socio-demographic factors predominantly affect the burden of malaria at household level. 11 Ethiopia has made notable progress in decreasing the prevalence and burden of malaria through public health measures taken during the millennium development goals (MDGs) era.…”
Section: Introductionmentioning
confidence: 99%
“…Health workers may not be prescribing appropriate antimalarials because the appropriate dosage or suspension is not available, because of provider or patient preference for alternative medications, or because of high out-of-pocket costs for these medications [ 49 – 51 ]. Some studies have found that patients continue to face out-of-pocket costs for health services and commodities that are intended to be provided free in settings similar to the study countries [ 52 54 ]. Continued improvements in the quality of care for malaria will require a deeper investigation into the lingering barriers and facilitators of appropriate clinical management of the disease.…”
Section: Discussionmentioning
confidence: 99%